Magnetically Responsive Microflaps Reveal Cell Membrane Boundaries from Multiple Angles. (22nd February 2014) - Teshima, Tetsuhiko; Onoe, Hiroaki; Aonuma, Hiroka; Kuribayashi‐Shigetomi, Kaori; Kamiya, Koki; Tonooka, Taishi; Kanuka, Hirotaka; Takeuchi, Shoji
<x xml:space="preserve">Abstract</x> A microflap system to incline adherent cells in the desired orientation is described. Inclination angles of cell‐laden microflaps are precisely controlled by the applied magnetic field, enabling us to observe cell‐membrane boundaries from multiple angles. This system is equipped with conventional microscopes, allowing clear focused images of cell‐membrane boundaries to be obtained with high magnification. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>